Job Market Signaling with Human Capital Investment - LEE, Gea Myoung (Institutional Knowledge at Singapore Management University, 2014)
In this paper, we consider the social value of signaling by recasting the Spence's (1973) signaling model in a causal relationship: human capital investment is necessary to reduce the marginal cost of signaling. Our model contains distinct features: (i) the choice of signaling a§ects the level of human capital investment and (ii) the proportion of high and low type in the entire workers is endogenously determined. From the perspective of welfare, we compare two contrasting forms of signaling, separating and pooling, and Önd that the choice of a proper form of signaling is dependent on how each signaling induces the human capital investment. We identify circumstances where it is socially beneficial to stay with a separating signaling and focus on promoting the human capital investment, and where it is socially beneficial to switch from a separating signaling to a pooling signaling and moderate the investment level.